Malaysia Political Changes Amid Covid-19 - Mohd Rizal Yaakop; Sharifah Aluya Alinda Dewi Syed Ali; Roslizawati Taib; Ahmad Redzuan Mohamad; Mohd 'Azmi Mohd Razif (Human Resource Management Academic Research Society, 2025)
International Journal of Academic Research in Business and Social Sciences Vol. 10, No. 12( Page: 224 - 233)